Does tax revenue spur the economic growth: empirical evidence from sri lanka. - Neruja, N. (University of Jaffna, 2019)
The relationship between economic growth and tax revenues is a debating issue among the researchers for a long period. The fiscal policy plays a significant role in economic growth in every country. Fiscal deficit is a chronic problem for many countries including Sri Lanka. This paper investigates the impact of direct tax revenue and indirect tax revenue on economic growth of Sri Lanka by using time series data for the period of 1990-2017. Growth of RGDP is taken as dependent variable while direct and indirect tax revenue, gross capital formation and human capital as independent variables. After checking the stationary of the variables (through ADF test), Autoregressive Distributive Lag (ARDL) approach to co integration is used to find association among variables. In the long term analysis, a relationship between indirect tax revenue with economic growth has a negative relationship. But Direct tax revenue statistically insignificant in long run and short run. Further, human capital is negatively correlated to economic growth in the long run and short run while gross capital formation positively affects the economic growth. Diagnostic tests confirm that our model is free from hetroskedasticity and autocorrelation with satisfactory functional form. The CUSUM show that model is structurally stable. Thus, the policy makers should reform the tax policy in order to promote the economic prosperity of the country as well as the fiscal consolidation since currently contribution of indirect taxes outweigh (20% of total) the direct taxes (80% of total).
Keywords: Tax revenue; Economic growth; Endogenous growth theory; ARDL